Dynamic role authorization in multiparty conversations. (July 2016) - Ghilezan, Silvia; Jakšić, Svetlana; Pantović, Jovanka; Pérez, Jorge; Vieira, Hugo
Abstract Protocols in distributed settings usually rely on the interaction of several parties and often identify theroles involved in communications. Roles may have a behavioral interpretation, as they do not necessarily correspond to sites or physical devices. Notions ofrole authorization thus become necessary to consider settings in which, e.g., different sites may be authorized to act on behalf of a single role, or in which one site may be authorized to act on behalf of different roles. This flexibility must be equipped with ways of controlling the roles that the different parties are authorized to represent, including the challenging case in which role authorizations are determined only at runtime. We present a typed framework for the analysis of multiparty interaction with dynamic role authorization and delegation. Building on previous work on conversation types with role assignment, our formal model is based on an extension of the $${π}$$ π -calculus in which the basic resources are pairs channel-role, which denote the access right of interacting along a given channel representing the given role. To specify dynamic authorization control, our process model includes (1) a novel scoping construct for authorization domains, and (2) communication primitives for authorizations, which allow to pass around authorizations to act on a given channel. An authorization error then corresponds to an action involving a channel and a role not enclosed by an appropriate authorization scope. We introduce a typing discipline that ensures that processes never reduce to authorization errors, including when parties dynamically acquire authorizations.